Part A: General overview of Regulatory Affairs/ Part B: A comparison of the CMC regulatory submission requirements in Europe and USA for small molecules and Biologics - Perera, Uduwa (Roshane) (2023)
Part A: The European Medicines Agency (EMA) requires an Investigational Medicinal Product Dossier (IMPD) to be submitted for the initiation of a clinical trial for a medicinal product in Europe. In the USA, an Investigational New Drug (IND) application needs to be submitted. The harmonised Common Technical Document (CTD) format set by the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) has made it easier for the multiple submissions of these applications to different regulatory authorities. Module 3 of the CTD relates to quality of the medicinal product and this is separated into two parts: drug substance and drug product. The body of data concerning Module 3 of the CTD for small molecules and biologics are the same, but the information required for these medicinal products due to the guidelines set by the EMA and the FDA. The Chemistry, Manufacturing and Controls (CMC) information needs to be updated at the beginning of each phase of a clinical trial. Generally, basic information is supplied at Phase I and the CMC requirements needed for Phase I application submissions to the Europe and USA are specifically considered in this second part of Review of Regulatory issues, building on the more general Review of Part A. For small molecules, the Module 3 requirements by the EMA and the FDA are similar with differences arising around the information required for Manufacture and Stability sections of the drug substance and the drug product parts. This was observed for the biological medicinal products as well, and it was also seen that usually the EMA requires detailed information in some sections compared to the FDA. The content and format of the IND guidance for Phase I studies set by the FDA has not updated since 1995, therefore the information required for IND applications is basic with no future amendment requirements for some sections of the IND. In contrast, the EMA continues to update their guidance documents regularly. Although the applications can be submitted simultaneously to different regulatory authorities with a standardised format, the information requested by these authorities are different for each medicinal product.